Discourses of betterment and opportunity: exploring the privileging of university attendance for first-in-family learners. Issue 6 (3rd June 2018) - O'Shea, Sarah; Stone, Cathy; Delahunty, Janine; May, Josephine
ABSTRACT: Much of the literature on university access and participation positions people from disadvantaged backgrounds as those who have not 'traditionally' attended university. Certain student cohorts are presented as lacking the skills or requisite knowledges to achieve academic success, requiring additional assistance from institutions to address these gaps. Rather than approach such students from a position of 'lack', this article problematises the concept of privilege, particularly as this relates to the perceived benefits of university attendance. Drawing on rich qualitative interviews with first-in-family students, this article discusses the nature of these learners' expectations of university, particularly those related to the promise of a more secure financial future. In unpacking these constructs and interrogating the ways in which higher education sectors are located within discourses of betterment and opportunity, deep insight is offered into the embodied and experiential nature of university for these students and their families.